Predictors of malignant brain edema after mechanical thrombectomy for acute ischemic stroke. (23rd February 2019) - Huang, Xianjun; Yang, Qian; Shi, Xiaolei; Xu, Xiangjun; Ge, Liang; Ding, Xianhui; Zhou, Zhiming
Abstract : Background: Malignant brain edema (MBE) is a devastating complication in ischemic stroke. Data on MBE in patients who have had mechanical thrombectomy (MT) are relatively scarce. Objective: To investigate the incidence, predictors, and clinical outcomes of MBE in patients after MT. Methods: We included 130 consecutive patients after MT caused by anterior circulation large vessel occlusion stroke, treated with MT. MBE was defined as a midline shift of ≥5 mm on the follow-up imaging within 72 hours after MT. Characteristics of patients at admission and details of treatment were collected. The 90-day modified Rankin scale score was used as a measure of functional outcomes. Results: Of the 130 patients (age, 68.6±10.9 years; male, 50%), 35 (26.9%) patients developed MBE. The patients with MBE had a lower rate of functional independence (OR=7.831; 95% CI 1.731 to 35.427; p=0.008) and significantly higher mortality at 90 days (OR=7.958; 95% CI 2.274 to 27.848; p=0.001) than patients without MBE. In 104 (80%) patients with successful recanalization (modified Thrombolysis in Cerebral Infarction score of 2b–3), 24 (23.1%) patients exhibited MBE. After adjustment for confounding, ICA occlusion (OR=3.746; 95% CI 1.169 to 12.006; p=0.026) and worse collateral score (grade 1 vs grade 0: OR=0.727; 95% CI 0.192 to 2.753; p=0.638; grade 2 vs grade 0: OR=0.130; 95% CI 0.021 to 0.819; p=0.030) were significantly associated with the development of MBE, despite successful recanalization. Conclusions: MBE after MT is not uncommon and was related to poor functional outcomes. Localization of a vessel occlusion and collateral status may play a role in the development of MBE.